Understanding the experiences of married Southern African women in protecting themselves from HIV/AIDS: a systematic review and meta-synthesis. Issue 6 (18th August 2019) - Timba-Emmanuel, Tabeth; Kroll, Thilo; Renfrew, Mary J; MacGillivray, Steve
ABSTRACT: Background: Whilst marriage has been repeatedly identified in the literature as an HIV risk factor amongst Southern African women, not much is known about women's perception of their role, experiences and strategies used to address HIV risks in the context of a marriage. Aims: The aim of the study was to synthesise perceptions, experiences and strategies of married Southern African women in the prevention of HIV. Methods: A systematic review of qualitative studies was conducted. Three electronic databases (Medline, Cinahl and PsycINFO) were systematically searched to identify relevant literature. The meta-synthesis process followed Sandelowski and Barroso's [2007. Handbook for Synthesizing Qualitative Research. Springer Publishing Company] recommendations. Results: Of 7 609 papers, 15 were included in the review. The quality of the included studies was variable. In the final synthesis stage, three broad analytic themes emerged: contextual background, cues to preventive behaviour, and HIV prevention strategies. Implications: Findings were used to develop a conceptual framework for studying HIV/AIDS prevention experiences of married Southern African women.